Penerapan E-Commerce Untuk Penjualan Furniture Pada UD. Tunggal Saudara - Wahyu Kristanto; Emmy Wahyuningtyas; Noven Indra Prasetya (Informatics Engineering Department-UWKS, 2017)
UD.Tunggal Brothers is a company engaged in the sale of furniture in Gresik. Products are offered in the form of Learning Table, Chairs, Kitchen Set, Room Set, Computer Furniture, spring bed, TV shelf, Sofas, Cabinets, Office Furniture, etc. Sales system used in UD.Tunggal you now still conventional.Other than UD.Tunggal you still have a system which is user admin example using the recording media to report sales resulting mismatch between sales report with the goods sold. System development in this research using the data collection phase, Systems Analysis, Systems Design, Construction Systems, Testing, and Documentation. The programming language used is PHP's database MySQL.Penelitian produces an application that is able to provide information about the product - the product offered by the Civil UD.Tunggal and provide convenience in product management and transactions. One type of technology implementation in terms of increased sales of the product is to use electronic commerce (e-Commerce) that can help market a wide range of products.